Sentidos sobre o trabalho pedagógico das professoras de bebês no município de Santa Maria/RS - Nascimento, Marina Ramos de Carvalho do (2024)
This dissertation is part of Research Line 2: Educational Policies, Educational Practices and their Interfaces, of the Postgraduate Program in Education (PPGE), of the Federal University of Santa Maria (UFSM), as well as in the studies of Kairós - Group of Studies and Research on Work, Education and Public Policies. The theme of this work is Early Childhood Education and pedagogical work with babies, in order to respond to the following question: using documentary analysis and interviews with baby teachers as a reference, what are the meanings of pedagogical work in public schools in the municipality of Santa Maria/RS? The objective was to analyze the meanings of the pedagogical work of nursery teachers in public schools in the municipality of Santa Maria in Rio Grande do Sul, based on interviews and documentary analysis. For the production and analysis of data, the theoreticalmethodological contribution was sought from the Analysis of Movements of Senses (AMS). During the research, the works already produced with this theme were mapped, totaling 7 researches, including theses and dissertations, in the Capes Catalog of Theses and Dissertations. Also, the Pedagogical Political Projects (PPP) of the institutions that participated in the research were mapped, the guiding document for the pedagogical work, as well as the documents, highlighting the National Curricular Guidelines for Early Childhood Education (2009), National Common Curricular Base (2017), Gaúcho Curricular Reference (2018) and the municipality's Curricular Guiding Document (2019). This movement of analyzing public policies, pedagogical projects and teachers' speeches highlighted three meanings about pedagogical work with babies: a) practice, b) absence and c) autonomy. These meanings constitute fundamental elements to understand, in the teachers' discourse, the dynamics and perspectives of pedagogical work with babies in public schools in the city of Santa Maria/RS.